Genome-wide analysis and expression profiling of the HD-ZIP gene family in kiwifruit - Kai-yu Ye; Jie-wei Li; Fa-ming Wang; Jian-you Gao; Cui-xia Liu; Hong-juan Gong; Bei-bei Qi; Ping-ping Liu; Qiao-sheng Jiang; Jian-min Tang; Quan-hui Mo (BMC Genomics, 2024)
Abstract The homeodomain-leucine zipper (HD-Zip) gene family plays a pivotal role in plant development and stress responses. Nevertheless, a comprehensive characterization of the HD-Zip gene family in kiwifruit has been lacking. In this study, we have systematically identified 70 HD-Zip genes in the Actinidia chinensis (Ac) genome and 55 in the Actinidia eriantha (Ae) genome. These genes have been categorized into four subfamilies (HD-Zip I, II, III, and IV) through rigorous phylogenetic analysis. Analysis of synteny patterns and selection pressures has provided insights into how whole-genome duplication (WGD) or segmental may have contributed to the divergence in gene numbers between these two kiwifruit species, with duplicated gene pairs undergoing purifying selection. Furthermore, our study has unveiled tissue-specific expression patterns among kiwifruit HD-Zip genes, with some genes identified as key regulators of kiwifruit responses to bacterial canker disease and postharvest processes. These findings not only offer valuable insights into the evolutionary and functional characteristics of kiwifruit HD-Zips but also shed light on their potential roles in plant growth and development.